CONSTRUCTIVE ANALYSIS OF PLATE COLUMNS - Askarov Xasanjon Abduqaxorovich; Karimov Ikromali.Tojimatovich; Iminjonov Islomiddin (American Journals Publishing, 2024)
In the article fractionation in a rectification column in a laboratory device separation methods are studied. Separator rectification using steam the construction of the column, the principle of operation is given. Rectification column allowing separation of acetic acid without losses in continuous operation.plate constructions are studied.
Keywords: Rectification, column, plate, heat exchange, ethyl acetate, steam, contact surface, grid.